The Differences of Wearing Shoes and Barefoot on Lower Limb Muscle Functions in Martial Arts Athletes of University - Tae-whan Kim; Tae-hyun Lee; Tae-beom Seo; JI-hoon Cho; Ki-hyuk Lee; Jong-baek Lee (Asian Society of Kinesiology, 2018)
OBJECTIVES The purpose of this study was to examine the differences of wearing shoes and barefoot on lower limb muscle functions in martial arts athletes of university. METHODS Fourteen martial arts athletes participated in this study. Lower limb muscle functions (maximum strength, power, and electromyography) and balance were measured when wearing shoes (WS) and barefoot (BF). Measured data were analyzed using IBM SPSS Statistics ver. 23.0 (IBM Co., Armonk, NY, USA). Paired t-test was used for comparison between WS and BF. RESULTS Maximum muscle strength (absolute and relative squat 1RM) and static balance (Standing on one leg with eyes close) were significantly higher in BF compared to WS. Although maximum muscle power and dynamic balance were higher in BF compared to WS, were non-significant. Muscle activities of rectus femoris and vastus lateralis were higher during WS than BF. CONCLUSIONS The results of this study suggest that Application of barefoot training seems to be effective on expression of lower limb maximum muscle strength and static balance in martial arts athletes of university.